Supervision of The Campaign Stages In The Election of Regional Heads In Banjarbaru, Indonesia - Normadina Normadina; Budi Suryadi; Andi Tenri Sompa (Wadah Inovasi Indonesia, 2021)
This study aims to analyze the supervision of Bawaslu of Banjarbaru City in the campaign stage on the installation of Props for the 2020 Election Campaign in Banjarbaru City. The results showed that Bawaslu's supervision of the installation of campaign props was carried out in the form of prevention and enforcement supervision. Supervision in the prevention of violations of the provisions in the installation of campaign props is to provide socialization to the candidate pairs and the campaign team of the candidate pairs. The socialization is aimed at obtaining a common understanding regarding the provisions and rules for the installation of campaign props. Supervision in the form of action is carried out synergistically with the relevant parties, be it the Banjarbaru City KPU, the Banjarbaru City Government, and the Candidate Pair for the Campaign Team of the candidate pairs in the 2020 Banjarbaru Mayor and Deputy Mayor Election. Constraints faced by Bawaslu in supervising the installation campaign props include the existence of a candidate pair's campaign team that has not been able to accept the various provisions and rules that have been set. Based on the results of the study, it was concluded that the supervision of the Banjarbaru City Bawaslu in the campaign stage on the installation of the 2020 Pilkada Campaign Props in Banjarbaru City had gone well, and the obstacle faced by Bawaslu was that there were still different understandings between the organizers and the campaign team of the candidate pairs. So it is recommended to the organizers of the regional head election to provide more intensive socialization to reach a mutual understanding regarding the various rules and regulations that apply.